Disease Burden Affects Outcomes in Pediatric and Young Adult B-Cell Lymphoblastic Leukemia After Commercial Tisagenlecleucel: A Pediatric Real-World Chimeric Antigen Receptor Consortium Report. Issue 9 (20th March 2022) - Schultz, Liora M.; Baggott, Christina; Prabhu, Snehit; Pacenta, Holly L.; Phillips, Christine L.; Rossoff, Jenna; Stefanski, Heather E.; Talano, Julie-An; Moskop, Amy; Margossian, Steven P.; Verneris, Michael R.; Myers, Gary Douglas; et al.
Abstract : PURPOSE: Tisagenlecleucel is a CD19-specific chimeric antigen receptor T-cell therapy, US Food and Drug Administration–approved for children, adolescents, and young adults (CAYA) with relapsed and/or refractory (RR) B-cell acute lymphoblastic leukemia (B-ALL). The US Food and Drug Administration registration for tisagenlecleucel was based on a complete response (CR) rate of 81%, 12-month overall survival (OS) of 76%, and event-free survival (EFS) of 50%. We report clinical outcomes and analyze covariates of outcomes after commercial tisagenlecleucel. METHODS: We conducted a retrospective, multi-institutional study of CAYA with RR B-ALL across 15 US institutions, who underwent leukapheresis shipment to Novartis for commercial tisagenlecleucel. A total of 200 patients were included in an intent-to-treat response analysis, and 185 infused patients were analyzed for survival and toxicity. RESULTS: Intent-to-treat analysis demonstrates a 79% morphologic CR rate (95% CI, 72 to 84). The infused cohort had an 85% CR (95% CI, 79 to 89) and 12-month OS of 72% and EFS of 50%, with 335 days of median follow-up. Notably, 48% of patients had low-disease burden (< 5% bone marrow lymphoblasts, no CNS3, or other extramedullary disease), or undetectable disease, pretisagenlecleucel. Univariate and multivariate analyses associate high-disease burden (HB, ≥ 5% bone marrow lymphoblasts, CNS3, or non-CNS extramedullary) with inferior outcomes, with a 12-month OS of 58% and EFS of 31% compared with low-disease burden (OS; 85%, EFS; 70%) and undetectable disease (OS; 95%, EFS; 72%; P < .0001 for OS and EFS). Grade ≥ 3 cytokine release syndrome and neurotoxicity rates were 21% and 7% overall and 35% and 9% in patients with HB, respectively. CONCLUSION: Commercial tisagenlecleucel in CAYA RR B-ALL demonstrates efficacy and tolerability. This first analysis of commercial tisagenlecleucel stratified by disease burden identifies HB preinfusion to associate with inferior OS and EFS and increased toxicity. Abstract :